Preliminary Study on Morphology, Meristics, and Morphometric Variations of Javan Spitting Cobra Naja sputatrix Boie, 1827 and Sumatran Spitting Cobra Naja sumatrana Müller, 1890 - Dafa, Maula Haqul; Yudha, Donan Satria; Sulistio, Adian Dwi (Generasi Biologi Indonesia, 2023)
Cobras are venomous snakes from Elapidae Family widespread in Asia and Africa, including Indonesia. There are two species of cobras in Indonesia, the one being is Javan spitting cobra (Naja sputatrix Boie, 1827) and other is Sumatran spitting cobra (Naja sumatrana Müller, 1890). In Indonesia, N. sputatrix distributions are in Java, Bali, and Nusa Tenggara, meanwhile N. sumatrana spread across Sumatra and Kalimantan. Wide distribution means that there are also potentially wide variations in morphology, meristic, and morphometric characters. This research was conducted to determine variations of Javan and Sumatran spitting cobra with morphology, meristic, and morphometric characterization. Total number of 16 samples (N. sputatrix = 8, N. sumatrana = 8) were examined and measured. Visual observation focused on coloration and hood characteristics. Meristic observation uses head, dorsal, ventral, and subcaudal scalation. Morphometric observation measures SVL, TL, Tail, and HW. We found that hood morphology varies greatly between N. sputatrix and N. sumatrana. N. sumatrana differs between Sumatran and Borneo population. Morphometric variation is being less prominent with morphometric description that matches with previous literatures and researches.